Correlation between Knowledge and Hesitancy towards COVID-19 Vaccine in Pregnant Women in The Working Area of Ranomeeto Health Centre - Yusril Marhaen; Juminten Saimin; Sulastrianah (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: Acceptance or refusal of vaccinations can be influenced by hesitancy about the COVID-19 vaccine. Hesitancy is determined by knowledge, attitudes, practices, and public concerns about the safety, efficacy, risks, and benefits associated with the COVID-19 vaccination program. Purpose: To determine the association between knowledge and hesitancy about the COVID-19 vaccine in pregnant women in the Ranomeeto Health Center Working Area. Methods: This is an analytic observational study with a cross-sectional approach. This study was conducted at the Ranomeeto Health Center, Konawe Selatan District. The number of samples is 77 people, collected by purposive sampling technique. Knowledge was measured using a knowledge questionnaire about the covid-19 vaccine. Hesitation was measured using a questionnaire about the COVID-19 vaccine. Data were collected and analyzed using the Chi-Square statistical test with a significance value of p<0.05. Results: The results showed that most pregnant women had good knowledge about the COVID-19 vaccine (42.9%) and had no hecitation about the COVID-19 vaccine (61.0%). Statistical tests obtained a significant p-value between knowledge and hesitancy about the COVID-19 vaccine (p=0.010). Conclusion: There is a significant correlation between knowledge and hesitancy about the COVID-19 vaccine in pregnant women in the Working Area of the Ranomeeto Health Center.